Leisure in Time Budgets of Soviet Citizens in1920s — Early 1930s - I. V. Sidorchuk (Научный диалог)
The issues of studying the time budgets of various categories of the Soviet population in the 1920s — early 1930s is examined in the article. Special attention is paid to the role of leisure in the everyday life of the Soviet person and the reasons for its insufficient prevalence. The results of a comparative analysis of materials on the study of the role of leisure in the time budgets of workers, students, engineers, party workers are presented. The question is raised about the difference in the place of leisure in the time budgets between men and women, as well as residents of capitals and provinces. The provisions and methods of historical anthropology, the history of everyday life and leisure, problem-chronological and comparative-historical methods are used the article. A review of the general and specific features for various categories of the population in the time spent on leisure has been carried out.  An assessment of the degree of representativeness of the results of the studies of time budgets carried out in the period under consideration is given. It is concluded that the time that the legislation relied on for rest in practice was either engaged in work or wasted unproductively. It was proved that the main reasons for this were the irregularity of the working day, additional work and irrational organization of free time.